Facile synthesis of 1,3,7-trihydroxyxanthone and its regioselective coupling reactions with prenal: simple and efficient access to osajaxanthone and nigrolineaxanthone F - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2006)
A facile five-step synthesis of naturally occurring 1,3,7-trihydroxyxanthone has been described starting from 1,3,5-trimethoxybenzene via NBS-induced nuclear bromination, lithiation followed by an in situ benzoylation with methyl 2,5-dibenzyloxybenzoate, selective deprotection of the two benzyl groups, base-catalyzed intramolecular cyclization, and demethylations pathway with 62% overall yield. The regioselective coupling reactions of 1,3,7-trihydroxyxanthone with prenal in the presence of calcium hydroxide at room temperature and under thermal conditions at 140-150 degrees C have been demonstrated to exclusively obtain the natural products osajaxanthone in 75% yield and nigrolineaxanthone F in 98% yield, respectively.

Facile chemo-, regio-, and diastereoselective approach to cis-3,5-disubstituted gamma-butyrolactones and fused gamma-butyrolactones - Baag, Md. Merajuddin; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
Chemoselective S(N)2' condensation of primary enolates of alkyl methyl ketones 2a-e with dimethyl bromomethylfumarate ( 1) followed by highly diastereoselective NaBH4 reduction of the ketone function in the formed ketodiesters 3a-e and the regioselective in situ lactonization of the unisolable intermediates 4a-e exclusively furnished the cis-3,5-disubstituted gamma-butyrolactones (+/-)-5a-e in very good yields. Similarly, the face-selective coupling reaction of cyclohexanone enolate with 1 to form a mixture of diastereomers in an 8: 2 ratio followed by a highly selective reductive cyclization of 9 plus 10 exclusively provided the cis-octahydrobenzofuran (+/-)- 12 in 70% overall yield.

Facile phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2+2] annulation reactions: an easy access to complex bioactive natural and unnatural benzopyran congeners - Mondal, Mukulesh; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2007)
The complex bioactive natural and unnatural benzopyran congeners have been synthesized using one-/two-step approaches in very good yields from the reactions of two different dihydroxyphthalides, natural resorcyclic acid derivative, and trihydroxybenzophenone with citral and/or farnesal, via the phenol-driven intramolecular diastereoselective thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions and three different thermal intramolecular cyclization reactions. The effects of the nature and the position of phenolic groups in the starting materials on the course of these cycloaddition reactions have also been described. Depending upon the absence or presence of intramolecular hydrogen bonding of the phenolic group with the carbonyl moiety in the starting materials, these phenol-driven intramolecular thermal/base-catalyzed dipolar [2 + 2] cycloaddition reactions either furnished the kinetically controlled products or directly formed the thermodynamically controlled rearranged products, respectively.

Facile air-oxidation of N-homopiperonyl-5,6-dimethoxyhomophthalimide: simple and efficient access to nuevamine - Wakchaure, Prasad B.; Easwar, Srinivasan; Puranik, Vedavati G.; N. P. Argade (Tetrahedron, 2008)
A facile six-step synthesis of naturally occurring (+/-)-nuevamine with 55% overall yield has been described, starting from methyl 2-(6-formyl-2,3-dimethoxyphenyl)acetate via the quantitative benzylic air-oxidation of the corresponding N-homopiperonyl-5,6-dimethoxy-homophthalimide to N-homopiperonyl-5,6-dimethoxyisoquinoline-1,3,4-trione as the key reaction, followed by base catalyzed regioselective alcoholysis of the trione with ring contraction, acid catalyzed dehydrative ring closure of the formed lactamol and decarboxylation pathway. (C) 2007 Elsevier Ltd. All rights reserved.

First ionic liquid-promoted Kabbe condensation reaction for an expeditious synthesis of privileged bis-spirochromanone scaffolds - Muthukrishnan, Murugan; Basavanag, U. M. V.; Puranik, Vedavati G. (Tetrahedron Letters, 2009)
A variety of privileged bis-spirochromanones were synthesized for the First time from 4,6-diacetyl resorcinol in one-pot by carrying out the Kabbe condensation in loom temperature ionic liquid [bbim]Br. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bis-spirochromanone; Ionic liquid; Kabbe condensation; Morpholine

Facile synthesis of N-benzylated 3-alkyl-2,6-diarylpiperidin-4-ones: Stereochemical investigation by 1D/2D NMR and single-crystal XRD - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2011)
A series of thirteen 1-benzyl-3-alkyl-2,6-diarylpiperidin-4-ones 14-26 were conveniently synthesized in high yields 87-92%. In order to find the impact on piperidone stereochemistry, beside the N-benzylation, methyl/ethyl/isopropyl groups at C-3 and halo/alkyl/alkoxy/benzyloxy groups on the phenyl rings at C-2/C-6 were introduced. All the synthesized compounds were characterized by mass, (1)H and (13)C NMR spectral studies. Of them, the 1-benzyl-3-ethyl-2,6-diphenylpiperidin-4-one 22 was completely characterized by 2D NMR techniques such as (1)H-(1)H COSY, (1)H-(13)C COSY and NOESY to assign the signals, unambiguously. The proton coupling constants and NOE correlations provided the complete stereochemistry of 22, which is further witnessed by its single-crystal XRD analysis. The NMR and XRD studies revealed that the compound 22 exists in a chair conformation with equatorial orientation of all the substituents in both solution and solid states. On the basis of their vicinal coupling constants, the chair conformation with equatorial orientation of the substituents at C-2, C-3, C-6 and N is proposed for all compounds 14-26; moreover, a considerable population of boat conformation also suggested for the compound 26 along with the predominant chair conformation, in solution. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2D NMR; Conformation; N-benzylation; Piperidin-4-one; single-crystal XRD; Stereochemistry

Ferrocene based organometallic gelators: a supramolecular synthon approach - Sahoo, Pathik; Puranik, Vedavati G.; Patra, A. K.; Sastry, P. U.; Dastidar, Parthasarathi (Soft Matter, 2011)
The supramolecular synthon namely primary ammonium dicarboxylate (PAD) synthon has been exploited to generate a new series of salt based low molecular weight gelators (LMWGs) derived from ferrocenedicarboxylic acid (FDCA) and primary amines Me-(CH2)(n)-NH2 (n = 3-15). While most of the salts are capable of forming gels with DMSO and DMF, nearly all of them show a tendency to form gels with at least one of the solvents studied. Structure property correlation based on single crystal and powder X-ray diffraction data in combination with optical-, scanning-, and transmission-electron microscopy reveals that the supramolecular synthon approach adopted herein for designing LMWGs is indeed useful and allows one to get an easy access to a new series of organometallic gelators.

First total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one: a cancer chemopreventive agent - Borikar, Sanjay P.; Paul, Vincent; Puranik, Vedavati G.; Sathe, Vilas T.; Lagunas-Rivera, Selene; Ordonez, Mario (Synthesis-Stuttgart, 2011)
The first total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one, a newly discovered natural product with anticancer property is described by two different routes. A sequence involving an incorporation of a methyl group via a Gilman reagent and a chemoselective reduction of a cyclic anhydride functionality are the key steps. The methods proposed start from easily available starting materials and allow ready preparation of the final compound in good overall yield.
Keywords: Allium cepa; chemopreventive; Gilman reagent; selective; synthesis

Formal synthesis of (-)-stemoamide using a useful epimerization at C-8 - Chavan, Subhash P.; Harale, Kishor R.; Puranik, Vedavati G.; Gawade, Rupesh L. (Tetrahedron Letters, 2012)
The formal synthesis of (-)-stemoamide was achieved starting from L-pyroglutamic acid. The key steps used are the allylation using BF3 center dot OEt2, ring closing metathesis, allylic oxidation and a novel epimerization at C8. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Allylation; Allylic oxidation; Pyroglutamic acid; Ring closing metathesis; Stemoamide

Formation of a pseudo-beta-hairpin motif utilizing the Ant-Pro reverse turn: consequences of stereochemical reordering - Nair, Roshna V.; Kotmale, Amol S.; Dhokale, Snehal A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2014)
Herein, we report a special case of pseudo-beta-hairpin formation by tetrapetide sequences featuring a two-membered Ant Pro dipeptide motif (Ant = anthranilic acid and Pro = proline) at the loop region. These folded structures uniquely feature the presence of C9- and C17-H-bonding patterns at reverse turn and interstrand regions, respectively. Their hairpin nucleation and folding propensities have been expounded using solution and solid state studies of distinct stereochemically altered sequences.

First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3